Phytochemical studies and biological activities of smilax myosotilora - Racheal, James (Universiti Malaysia Sarawak (UNIMAS), 2014)
Phytochemical studies have been carried out on the Smilax myosotiflora, which is commonly known as 'ubi jaga' in Malaysia, from the family Smilacaceae. Most of the phytochemical surveys carried out in this family were concentrated with sterol compounds. Besides that, other compounds present in the plant have been studies as well. The MeOH crude extract obtained is about 10.88g. Isolation was carried out using various chromatographic techniques. Compound isolated and purified using Thin layer Chromatography (TLC), Preparative thin layer chromatography (PTLC) and Column Chromatography (CC) technique. The pure compound was isolated namely /3-sitosterol. This structure compound were elucidated and characterized by spectroscopic analysis using 'H and ''C Nuclear Magnetic Resonance (NMR) Spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), and CHN Elemental Analyzer. Biological evaluations were carried out on the fractions and crude extracts. The results stated that the compound 1 has higher LC;) value that was 210.0 ppm. This higher value indicated that compound 1 has less toxicity against Artemia salina. The fraction 1 that has a compound 1 was the highest percentage of activity scanvenging among the entire fraction which is 93.15 %.